The Comparative Efficacy of Endometrial Biopsy using Pipelle and Diagnostic Dilatation & Curettage in Mariano Marcos Memorial Hospital and Medical Center - Melody Nethania Sutedja; Ruth Judith Gay V. Cristobal; Maria Constancia Celina C. Ferraris; Czarina Juliana L. Alcaraz; Gisele V. Gonzales-Acantilado (HM Publisher, 2023)
Background: The use of Pipelle sampling for endometrial histology and pathology is of some controversy - and vast importance. Pipelle procedures are performed commonly in medical offices when women show abnormal vaginal bleeding. While the method has several advantages over dilatation and curettage (D&C), clinical questions exist on the precision and accuracy of the procedure. This study aimed to assess the effectiveness of Pipelle biopsy sampling versus Dilatation & Curettage (D&C) in adequacy of sampling specimen in terms of cost effectiveness, diagnosis success rate, sensitivity, specificity, positive predictive value, and negative predictive value. Methods: A retrospective study was conducted among all enrolled women with abnormal uterine bleeding counselling outpatient and inpatient in MMMHMC Batac from 2016 to 2017. Sample was divided in two groups - those that underwent Pipelle biopsy and those who underwent D&C. Key statistics were computed using SPSS 16. Results: Cost effectiveness analysis showed that Pipelle biopsy offers a more cost effective alternative with an estimate of one correct diagnosis every P16 spent versus P61 spent for a correct diagnosis using D&C. Both procedures resulted in a 100% likelihood ratio of having the condition with a positive test result, with D&C resulting in a higher diagnosis success rate of 98% (versus 92% for Pipelle) and higher proportion of those who have the disorder, given the procedure tested positive. Conclusion: Pipelle biopsy offers a more cost effective alternative to D&C. Both procedures resulted in equal probability of having the condition with a positive test result, with D&C resulting in a higher success rate of diagnosis and sensitivity rate, albeit not statistically significant.